Forensic investigation of 23 autosomal STRs and application in Han and Mongolia ethnic groups - Xiang Sheng; Yali Wang; Jiashuo Zhang; Liqin Chen; Yuan Lin; Zhenmin Zhao; Chengtao Li; Suhua Zhang (Oxford University Press, 2018)
A forensic validation study of the Early Access Huaxia™ Platinum Polymerase Chain Reaction (PCR) kit was completed to document the performance capabilities and limitations. The genotyping of DNA samples was consistent across a large range of template DNA concentrations, with complete profiles obtained at 0.125 ng; however, no more than 2 mm × 1.2 mm punches of samples would be recommended for direct amplification. The size precision and accuracy test revealed the genotyping ability; while consistent results were obtained when comparing the kit with other commercially available systems. In addition, the whole PCR amplification can finish within approximately 45 min, making the system suitable for fast-detection. However, only partial profiles may be obtained with challenging samples, including DNA stored on Foam-Tipped Applicators (FTA) cards or some case samples. For the forensic application in ethnic groups, a total of 282 and 229 alleles were obtained in Han and Mongolia, respectively. Since the 23 short tandem repeats were independent from each other, the cumulative power of exclusion in duos was 0.999 999 157 188 and the cumulative power of exclusion in trios was 0.999 999 999 859 in the Han group while the cumulative power of exclusion in duos (CPEduo) was 0.999 998 848 26 and cumulative power of exclusion in trios (CPEtrio) was 0.999 999 999 79 in the Mongolia group. And good internal consistency was found between the two investigated groups and the Sichuan Han, Hui, Tibetan and Uygur according to available reference data.